2019
DOI: 10.1038/s41598-019-43681-x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of drug-eluting stenting compared with bypass grafting in diabetic patients with multivessel and/or left main coronary artery disease

Abstract: Although percutaneous coronary intervention (PCI) with drug-eluting stents (DESs) and bypass grafting are generally believed to be superior revascularization strategies in patients with coronary artery disease (CAD), the optimal strategy for diabetic patients is still controversial. This meta-analysis was performed to compare two methods of revascularization for patients with diabetes mellitus with left main coronary artery lesions or disease in multiple coronary arteries. Compared with the coronary artery byp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
0
5
2
Order By: Relevance
“…Other studies comparing PCI and CABG in diabetics patients also revealed similar results as our meta-analysis in terms of all-cause mortality, MACCE, cardiac death, revascularization rate, MI development and CVA [48] , [49] , [50] . However, two previous meta-analyses showed all-cause mortality was not statistically significantly between both procedures in diabetic patients with multivessel or left main CAD [51] , [52] but had much lower sample size compared to our study. Nevertheless, these studies still revealed significant reduction in MACCE, cardiac death, MI and revascularization rate in patients undergoing CABG [51] , [52] .…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…Other studies comparing PCI and CABG in diabetics patients also revealed similar results as our meta-analysis in terms of all-cause mortality, MACCE, cardiac death, revascularization rate, MI development and CVA [48] , [49] , [50] . However, two previous meta-analyses showed all-cause mortality was not statistically significantly between both procedures in diabetic patients with multivessel or left main CAD [51] , [52] but had much lower sample size compared to our study. Nevertheless, these studies still revealed significant reduction in MACCE, cardiac death, MI and revascularization rate in patients undergoing CABG [51] , [52] .…”
Section: Discussioncontrasting
confidence: 86%
“…However, two previous meta-analyses showed all-cause mortality was not statistically significantly between both procedures in diabetic patients with multivessel or left main CAD [51] , [52] but had much lower sample size compared to our study. Nevertheless, these studies still revealed significant reduction in MACCE, cardiac death, MI and revascularization rate in patients undergoing CABG [51] , [52] .…”
Section: Discussioncontrasting
confidence: 86%
“…CABG is more invasive than PCI and has a higher risk of adverse cerebral vascular events during perioperative period [32]. Although PCI is more likely to be associated with higher rate of adverse events after revascularization, previous studies [13] have reported no difference in mortality between PCI and CABG and CABG was associated with excess stroke [33, 34], making it difficult for physicians to assess the two strategies. This study pooled data from 16 studies, which included 18,224 diabetic patients (follow-up ≥ 1 year) with left main CAD and/or MVD, undergoing either PCI or CABG.…”
Section: Discussionmentioning
confidence: 99%
“…Mahmoud et al [36] compared the clinical outcomes between these two strategies found that PCI was associated with a lower early risk of MACCE, while the risk of all-cause mortality, MI, and stroke were similar to CABG at long-term follow-up. Additionally, an in-depth comparative study of patients with DM [12] found that the risk of mortality (1–5 year follow-up) was not significantly different between PCI and CABG patients with DM; results that were supported by a recent study found no obvious difference in the incidence of all-cause mortality between the two strategies [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation